PENGARUH UPAH MINIMUM DAN TINGKAT PENDIDIKAN TERHADAP PENYERAPAN TENAGA KERJA DI SUMATERA SELATAN - Nurul Fauziah; Muhammad Rendy Putra Pratama Wijaya; Khoirunisyah; Redo Firmansyah; Maya Panorama (INUMIYA: Jurnal Ekonomi Pembangunan, 2023)
Labor absorption is very important in measuring the level of labor use in the economy. The demand for labor plays a key role in creating jobs and mitigating attrition. It also reflects how efficiently the economy utilizes available human resources. The method used in this research is a quantitative literature method using secondary data. In this research, the influence of the minimum wage and education level on work energy absorption is the main focus. The research results show that employment energy absorption in South Sumatra is still low, partly due to the dominance of the agricultural sector which has not yet adopted high technology. And the minimum wage level has a negative effect on labor absorption in South Sumatra. It is important to understand the factors that influence labor absorption and find appropriate solutions, such as qualifying the workforce, supporting industrial growth, and integrating technology in the agricultural sector, which can help increase employment opportunities and reduce poverty levels in the region. Apart from that, it is also important to take the right decision in setting the minimum wage level.